2022
DOI: 10.3390/microorganisms10050867
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Plant-Microbe Interactions between Endophytic Actinobacteria and Their Role in Plant Growth Promotion and Biological Control of Cotton under Salt Stress

Abstract: Bacterial endophytes are well-acknowledged inoculants to promote plant growth and enhance their resistance toward various pathogens and environmental stresses. In the present study, 71 endophytic strains associated with the medicinal plant Thymus roseus were screened for their plant growth promotion (PGP), and the applicability of potent strains as bioinoculant has been evaluated. Regarding PGP traits, the percentage of strains were positive for the siderophore production (84%), auxin synthesis (69%), diazotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 102 publications
1
1
0
Order By: Relevance
“…Numerous reports are available on their potential as agents for promoting plant growth [ 40 , 41 ]. Our results are in concordance with Mohamad et al (2022), who reported a significant increase in the total fresh weight of cotton plants under different salt conditions when the plants were inoculated with actinobacterial strains Streptomyces luteus XIEG05 and Nocardiopsis dassonvillei XIEG12 [ 42 ]. In the same way, the Streptomyces sp.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous reports are available on their potential as agents for promoting plant growth [ 40 , 41 ]. Our results are in concordance with Mohamad et al (2022), who reported a significant increase in the total fresh weight of cotton plants under different salt conditions when the plants were inoculated with actinobacterial strains Streptomyces luteus XIEG05 and Nocardiopsis dassonvillei XIEG12 [ 42 ]. In the same way, the Streptomyces sp.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, fungi release phytohormones, volatile chemicals, and siderophores, which can either indirectly or directly promote plant development by making their host more nutrient-available [ 48 ]. Several endophytic bacteria with valuable metabolites for agriculture and biotechnology are present in different medicinal plants [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…(2022) three endophytic bacteria were screened from the medicinal plant, Thymys roseus , demonstrating the capability to produce auxin and tolerate up to 200 µM NaCl stress. Upon inoculation of these bacteria into cotton plants, Streptomyces atrovirens exhibited the greatest increase in root length and weight compared to the control, while Alloactinosynne album caused the maximum increase in shoot length and weight ( Mohamad et al., 2022 ).…”
Section: Auxin-producing Endophytes and Their Potential Use In Drough...mentioning
confidence: 99%
“…Furthermore, their use can lead to unregulated or irregular plant growth tendencies, such as epinasty ( Bhojwani, 2012 ; Keswani et al., 2020 ) Another alternative approach involves the contribution of plant-associated beneficial microorganisms, which have been reported to augment auxin levels in plants ( Arshad and Frankenberger, 1991 ; Nassar et al., 2005 ; Tsavkelova et al., 2007 ; Shi et al., 2009 ; Keswani et al., 2020 ; Iqbal et al., 2023 ). Endophytic bacteria have been documented to promote plant growth in various crops including rice ( Walitang et al., 2017 ), wheat ( Yandigeri et al., 2012 ; Patel and Archana, 2017 ), maize ( Riggs et al., 2001 ), potato ( Nowak et al, 1995 ; Pavlo et al., 2011 ), cucumber ( El-Tarabily et al., 2009 ; Shaalan et al., 2021 ), cotton ( Bashan et al., 1989 ; Mohamad et al., 2022 ; Verma et al., 2022 ), tomato ( Pillay and Nowak, 1997 ; Agarwal et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%